Suppression of hepatic stellate cell activation through downregulation of gremlin1 expression by the miR-23b/27b cluster - Zeng, Xian-Yi (Oncotarget, 2016)
The imbalance between transforming growth factor β and bone morphogenetic protein 7 signaling pathways is a critical step in promoting hepatic stellate cell activation during hepatic fibrogenesis. Gremlin1 may impair the balance. Something remains unclear about the regulatory mechanisms of gremlin1 action on hepatic stellate cell activation and hepatic fibrosis. In the current study, gremlin1 overexpression promotes activation of hepatic stellate cells. Knockdown of gremlin1 with siRNAs suppresses hepatic stellate cell activation and attenuates hepatic fibrosis in rat model. Our results also show that miR-23b/27b cluster members bind to 3′-untranslated region of gremlin1 resulting in reduction of transforming growth factor β, α-smooth muscle actin and collagenI α1/2 gene expression. Our findings suggest that gremlin1 promotes hepatic stellate cell activation and hepatic fibrogenesis through impairment of the balance between transforming growth factor β and bone morphogenetic protein 7 signaling pathways. The miR-23b/27b cluster suppresses activation of hepatic stellate cells through binding gremlin1 to rectify the imbalance.